Study on the Impact Mechanism of Supply Chain Integration on Supply Chain Resilience - Luo, Fuhong (Transactions on Economics, Business and Management Research, 2024)
In recent years, the auto parts manufacturing industry has been facing multiple challenges, such as economic fluctuations, technological changes, etc. Improving SCR has become an urgent need for the development of the industry. This paper explores how automotive parts manufacturing companies can enhance supply chain resilience by optimizing SCI and analyze how this relationship changes in the context of market turbulence. The study shows that all three dimensions of SCI, namely supplier integration, internal integration and customer integration, can significantly enhance supply chain resilience. Relational capital and supply chain agility play an important role as mediating variables, while MT negatively moderates the supply chain integration and resilience relationship. This study not only deepens the theoretical understanding, but also provides new perspectives for practice, emphasizing that when formulating supply chain strategies, firms need to consider the multidimensional impact of integration to ensure the sustained stability and long-term competitiveness of the supply chain.